Characteristics of Patients with Diabetes Mellitus Regarding Efforts to Prevent Complications at the Internal Medicine Polyclinic - Zikran Zikran; Herliawati Herliawati; Tobi Pitora; Romy Suwahyu; Dhia Diana Fitriani; Desti Kurnia Utami (Jurnal Keperawatan Komprehensif (Comprehensive Nursing Journal), 2026)
Background: Diabetes mellitus is a chronic disease that can affect a patient's quality of life if not properly managed. Patients require long-term care, making the prevention of complications essential, given the high potential for diabetes mellitus to cause complications in any organ of the body. Objective: This study aimed to describe the characteristics of patients with diabetes mellitus in the context of efforts to prevent diabetes complications at an internal medicine outpatient clinic. Methods: This study employed a descriptive survey using a cross-sectional design. A sample of 84 respondents was selected using a non-random, purposive sampling technique. Data were collected using a questionnaire designed to assess the characteristics of patients with diabetes mellitus. Univariate analysis was performed following the data collection procedure. Respondents received a study explanation, and ethical research principles were upheld throughout the process. Results: Univariate analysis revealed the following profile of the diabetes mellitus patients: the majority were male (n=48; 57.1%) and aged between 45 and 64 years (n=47; 56.0%); the most common education level was junior high school (n=26; 31.0%); 19 respondents (22.6%) were civil servants; 31 respondents (36.9%) weighed between 61 and 80 kg; the majority (n=55; 65.5%) had a family history of diabetes mellitus; and the most common duration of the disease was 6–10 years (n=30; 35.7%). Conclusion: This study was limited to describing the characteristics of patients with diabetes mellitus regarding efforts to prevent complications; future research should investigate the relationship between these characteristics and the prevention of diabetes complications